Water Relations of Vitis vinifera L. cv. Sunred Seedless in Response to Soil Water Depletion Before Harvest - Myburgh, P.A.; Howell, C.L. (South African Journal of Enology and Viticulture, 2017)
Effects of soil water depletion level and irrigation cut off during ripening on water stress in Sunred Seedless table grapes were studied in a field trial in the Hex River Valley of South Africa. Water status of grapevines subjected to four irrigation treatments was determined prior to harvest during the 2000/01 season. Grapevines of all treatments were irrigated at 40% plant available water (PAW) depletion before véraison. From véraison, i.e. the onset of ripening in December, until harvest at the end of January, two treatments were irrigated at 20% and 40% PAW depletion, respectively. Two more treatments were applied by cutting off irrigation at 20% PAW depletion when total soluble solids reached 12°B and 15°B, respectively. Pre-dawn water stress in grapevines irrigated at 20% PAW depletion until harvest was less than in those where irrigation was cut off at 12°B. Sap flow measurements indicated that partial stomatal closure seemed to have occurred over the warmest part of the day. Apparently, stomatal control limited Ψl differences between treatments although extensive soil water depletion occurred where irrigation was cut off during ripening. If accumulated leaf water potential (ΨT) is considered, irrigation cut off at 12°B and 15°B induced more water stress in grapevines from 04:00 to 24:00 compared to those vines where irrigation was continued until harvest. Where irrigation was continued throughout the ripening period, the level of PAW depletion did not affect ΨT. However, during the sunshine period (08:00 until 18:00), ΨT in grapevines subjected to 40% PAW depletion, as well as those where irrigation was cut off, was higher than in the ones that were irrigated at 20% depletion until harvest. During the first half of the night, i.e. from 18:00 until 24:00, water potential in grapevines where irrigation was cut off at 12°B was unable to recover to the same level as in those exposed to the other treatments.